Produção e avaliação de proteína SeM recombinante para o controle de Adenite Equina - Moraes, Carina Martins de (2008)
Strangles is a contagious disease of the upper respiratory tract of horses caused by Streptococcus equi subsp. equi. Asymptomatic carriers responsible for maintaining the infection in the herd can only be detected by serological or microbiological methods and vaccines used for the control of the disease induce levels of protection generally not exceeding 50%. Considering that S. equi SeM protein is considered the most promising antigen to protect against the disease, this research aimed to produce and evaluate as antigen for vaccines and for ELISA, a recombinant S. equi SeM protein (rSeM). rSeM was produced by cloning and expression in Escherichia coli and purified by affinity chromatography. To test its immunogenicity isogenic female Balb-c mice 4-6 weeks-old were randomly divided and inoculated with 1 / 20th of the estimated dose of the vaccine for horses by the SC route, on days 0 and 21 of the experiment. One group was vaccinated with 250mL (12 mg mL-1) of rSeM without adjuvant, another with 300mL of vaccine containing 12 mg mL-1 of rSeM plus 20% of aluminiun hydroxide, two other groups were vaccinated with two commercial bacterins against Strangles, other two groups were vaccinated with the same commercial vaccines containing 12 mg mL-1 of rSeM and the remaining group was inoculated with a bacterin produced with a field strain. The control group was inoculated the same dose of sterile saline. Blood samples were collected from the retro-orbital venous plexus on days 0, 21, 42. The antibodies were titrated by ELISA using rSeM as antigen. rSeM was immunogenic for mice with a protection index of 100%. For the standardization of an ELISA, groups of 20 negative, vaccinated and positive animals were used. Using as Cut-off the mean plus two SD of the Optical Densities of the negatives, the test showed 100% sensitivity and specificity.